Application of Talaqqi Method in Learning Tahfidz Al-Qur'an in Early Children : Penerapan Metode Talaqqi dalam Pembelajaran Tahfidz Al-Qur’an pada Anak Usia Dini - Putri, Devi Nurdiana; Romadlon, Dzulfikar Akbar (Universitas Muhammadiyah Sidoarjo, 2023)
The talaqqi method is a method taught by the angel Gabriel to the Prophet Muhammad in conveying revelation, as when the first revelation, namely Surah al-Alaq verses 1-5 was revealed in Hiro Cave. The implementation of tahfidz Al-Qur'an using the talaqqi method, namely by means of a teacher reading the verse and students listening then following the reading and will be corrected by the teacher related to the errors that exist. supporting and inhibiting factors for the application of the talaqqi method in learning tahfidz Al-Qur'an at TPA Fafirruu Ilallah Surabaya. This study uses a qualitative research method that aims to describe the application of the talaqqi method in learning Tahfidz Al-Qur'an at the Fafirruu Ilallah Al-Qur'an Education Park in Surabaya. Data collection techniques used in this study were observation, interviews and documentation. The analysis techniques used are data collection, data presentation, and conclusions. Based on the results of the research that has been done, it is known that the application of the talaqqi method in learning tahfidz Al-Qur'an at the Fafirruu Ilallah Al-Qur'an Education Park Surabaya includes planning, implementation and evaluation. Planning includes the basis for choosing the method and preparing for the application of the method so that the method that has been chosen is not wrongly applied to children. The implementation of the talaqqi method in learning tahfidz Al-Qur'an is good, it's just that the implementation process is carried out classically so that it makes the class less conducive when the implementation process is carried out. Evaluation of the application of the talaqqi method in learning tahfidz Al-Qur'an is carried out through an evaluation of the memorization obtained by students. The supporting and inhibiting factors for students in learning tahfidz Al-Qur'an are located on the ability of the students themselves as well as the motivation and support of parents.